2019
DOI: 10.1101/579144
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Microbiological, biochemical, physicochemical surface properties and biofilm forming ability ofBrettanomyces bruxellensis

Abstract: Brettanomyces bruxellensis is a serious source of concern for winemakers. The production of volatile phenols by the yeast species confers to wine unpleasant sensory characteristics which are unacceptable by the consumers and inevitably provoke economic loss for the wine industry. This ubiquitous yeast is able to adapt to all winemaking steps and to withstand various environmental conditions. Moreover, the ability of B.bruxellensis to adhere and colonize inert materials can be the cause of the yeast persistence… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Although only a limited number of strains were tested, the beer group showed robustness regarding biofilm formation in glucose-rich or glucose-limited media. For other genetic groups, production of biofilm was more dependent on environmental characteristics, suggesting different regulatory mechanisms (Dimopoulou, Renault, et al, 2019). These differences were also partly mirrored by the biochemical and physicochemical properties of the surface of the strains (Dimopoulou, Renault, et al, 2019).…”
Section: Brettanomyces Bruxellensis Show Important Intraspecific Vari...mentioning
confidence: 99%
See 2 more Smart Citations
“…Although only a limited number of strains were tested, the beer group showed robustness regarding biofilm formation in glucose-rich or glucose-limited media. For other genetic groups, production of biofilm was more dependent on environmental characteristics, suggesting different regulatory mechanisms (Dimopoulou, Renault, et al, 2019). These differences were also partly mirrored by the biochemical and physicochemical properties of the surface of the strains (Dimopoulou, Renault, et al, 2019).…”
Section: Brettanomyces Bruxellensis Show Important Intraspecific Vari...mentioning
confidence: 99%
“…Intraspecific diversity was observed in the ability to enter or exit the VBNC state (Capozzi et al, 2016;Longin et al, 2016) as well as to form pseudohyphae (Martyniak et al, 2017) or biofilm (Joseph et al, 2007). Recently, two concomitant studies (Dimopoulou, Renault, et al, 2019;Lebleux et al, 2020) have suggested that the ability to produce biofilms depends on the genetic groups. Although only a limited number of strains were tested, the beer group showed robustness regarding biofilm formation in glucose-rich or glucose-limited media.…”
Section: Brettanomyces Bruxellensis Show Important Intraspecific Vari...mentioning
confidence: 99%
See 1 more Smart Citation